The Occupation of East Baitul Maqdis in the 1967’s Six Days Arab-Israeli War: Re-examining the British’s Reaction and Policy - Zakariah, Muhamad Hasrul (Journal of Al-Tamaddun, 2022)
This article re-examines the British’s policy and reaction towards the occupation of the East Baitul Maqdis during the Six Days Arab-Israeli War in 1967. As a result of the conflict, the Israelis regime annexed the eastern part of the City which was under the Jordanian’s control since 1948. Subsequently, Tel Aviv launched the process of ‘Israelization’ of the unified Baitul Maqdis by expropriating the Arab’s land and imposing the Israelis culture via education and administration means. Hence, this study will analyse the way London reacted towards the Israelis policy and action by comparing the official proclaimed policy such as the statement voiced by the Foreign Secretary at the parliament and at the United Nations with the actual reactions projected. The question on British’s actual stand is significant and interesting since Britain played an important role after the war such as drafting the UN Resolution 242 which temporarily ended the conflict. The analysis is relied upon mostly the declassified archival documents from the National Archive of the United Kingdom. In the finding, the article concluded that the British was inconsistent between its official policy and the actual reaction: consequently, this brings into question the veracity of equilibrium and impartiality principle of the British government during the Arab- Israeli War of 1967.